Progeria - Mohamed Riyaz S; Jayachandran S (Wolters Kluwer Medknow Publications, 2009)
Hutchinson Gilford Progeria Syndrome (HGPS) is a rare, sporadic, autosomal dominant syndrome that involves premature ageing and death at early age due to myocardial infarction or stroke. A 30-year-old male with clinical and radiologic features highly suggestive of HGPS is presented here with description of differential diagnosis, dental considerations and review of literature.